The Space for Restorative Justice in the Ethiopian Criminal Justice System - Enyew, Endalew Lijalem (Bergen Journal of Criminal Law & Criminal Justice, 2014)
Restorative Justice (RJ) is an alternative way of apprehending crime and justice which views crime as a violation of a relationship among victims, offenders and community, and which allows the active participation of the crime’s stakeholders. It has the objective of ‘putting right’ the wrong done, to restore the broken relationship and to reintegrate the offender back into society. The Ethiopian criminal justice system views crime primarily as a violation of the state’s criminal laws, either in the form of a commission or omission. It excludes the community from participation, and gives no opportunity to the victim to fully participate in the process. Nor is there a satisfactory legal procedure which enables the public prosecutor to adequately protect the victim’s interest. The focus of the public prosecutor is to have the accused convicted and punished, instead of encouraging them to take responsibility to undo the wrong they have committed. This article thus examines whether restorative justice has a place in the formal legal framework of the existing Ethiopian criminal justice system; and analyses the prospects for, and the challenges that may hinder, the implementation of restorative justice practice in this framework.